Grafting of natural rubber copolymer with ethyl methacrylate by gamma irradiation for using as soft lining denture base material - Somporn Swasdison (Chulalongkorn University, 2008)
Recently, natural rubber has been used in several medical products. The purpose of this study was to develop a soft lining material from natural latex which had been improved its physical, mechanical and biological properties. Initially, natural latex was vulcanized by gamma irradiation. The vulcanized latex was then grafted with ethyl methacrylate using gamma irradiation also. The grafted vulcanized rubber, so-called graft copolymer, was evaluated for its physical and mechanical properties as well as the cellular biocompatibility. Coe Supersoft, the commercial soft lining material, was used as a control. The results from physical and mechanical evaluation showed that the surface hardness and the tensile bond strength to the denture base material of both the graft copolymer and control material were not significantly difference (p>0.05) while the tensile strength and tear strength of graft copolymer were significantly higher than control group (p<0.05). In addition, the surface wettability of graft copolymer was better than Coe Supersoft and the water absorption of graft copolymer was lower than the control when both materials were immersed in water for 10 months. The result from in vitro study demonstrated that human gingival fibroblasts well proliferated and attached onto the surface of the graft copolymer while the cell co-cultured with the control material could not survive in the parallel experiment. These results suggested that grafting of ethyl methacrylate to the gamma irradiated vulcanized latex could improve the physical and mechanical properties as well as the cellular biocompatibility of the graft copolymer. Therefore, it would be worth to modify natural rubber with ethylmethacrylate grafting to be used as a denture soft lining materials.